Sustainability leadership and the protection of the common good - Wilson, Sam; John, Michele (Taylor and Francis, 2025)
In the context of concerns about the end of a safe operating space for humanity, there are calls for societies to evolve to preserve the socio-ecological systems that underpin our long-term well-being and to protect and preserve those elements of the common good that are critical to a sustainable future. However, it is also important to recognise that broad agreement about the existence and importance of addressing global common good problems, such as climate change, can obscure profound differences of opinion in how such problems ought to be understood and addressed – differences that can be revealed in surprising and striking ways when the real work of sustainability leadership begins.